The Use of Natural Ingredients as Topical Therapy for the Treatment of Second-Degree Burns: A Review Article - Ni Nyoman Ita Trisnadewi; Desak Ketut Ernawati; Agung Nova Mahendra (Riviera Publishing, 2026)
Second-degree burns are skin tissue damage involving the epidermis and part of the dermis, requiring appropriate treatment to prevent infection and accelerate tissue regeneration. Conventional therapy remains the primary choice, but long-term use can cause certain side effects. This situation has encouraged the increasing use of natural ingredients as alternative therapies because they are considered safer, easier to obtain, and contain bioactive compounds that support the wound healing process. This review article aims to assess the potential of various natural ingredients as topical therapies for healing second-degree burns. The method used is a literature review of research articles published between 2021 and 2026 through Google Scholar, PubMed, ScienceDirect, and DOAJ. The results of this study indicate that various plants such as kepok banana, moringa, breadfruit, red dragon fruit, and other herbal plants are effective in the burn healing process through various dosage forms such as creams, gels, ointments, spray gels, and nanogels. The dominant phytochemical compounds found include flavonoids, saponins, tannins, alkaloids, and terpenoids, which act as anti-inflammatory, antibacterial, and antioxidant agents. Overall, natural ingredients have the potential to be developed as an alternative treatment for second-degree burns that is effective and easily accessible to the public.